Local Institutions and Armed Group Presence in Colombia (2014)
This paper investigates the causal impact of non-state armed groups on local institutions during the armed conflict in Colombia, and tests competing theoretical mechanisms that may shape such effect. Our identification strategy is based on the construction of contiguous-pairs of rural communities that share common socio-economic characteristics but differ in armed group presence. The results show that the presence of armed groups is associated with increases in overall participation in local organizations, with a particularly strong effect on political organizations. This strengthening of local institutions during wartime appears to be driven by coercion exercised by armed groups that capture local organizations for strategic war purposes, rather than a reflection of a vibrant civil society